Mother-child interactions in adolescents with borderline personality disorder traits and the impact of early life maltreatment - Williams, Katharina; Fleck, Leonie; Fuchs, Anna; Koenig, Julian; Kaess, Michael (Child and adolescent psychiatry and mental health, 2023)
BACKGROUND: Early detection and intervention of borderline personality disorder (BPD) in adolescence has become a public health priority. Theoretical models emphasize the role of social interactions and transgenerational mechanisms in the development of the disorder suggesting a closer look at caregiver-child relationships. METHODS: The current study investigated mother-adolescent interactions and their association with adolescent BPD traits by using a case-control design. Thirty-eight adolescent patients with ≥ 3 BPD traits and their mothers (BPD-G) were investigated in contrast to 35 healthy control dyads (HC-G). Maternal, adolescent and dyadic behavior was coded using the Coding Interactive Behavior Manual (CIB) during two interactions: a fun day planning and a stress paradigm. Additional effects of maternal and/or adolescent early life maltreatment (ELM) on behavior were also explored. RESULTS: BPD-G displayed a significantly lower quality of maternal, adolescent and dyadic behavior than the HC-G during both interactions. Maternal and adolescent behavior was predicted by BPD traits alone, whilst dyadic behavior was also influenced by general adolescent psychopathology. Exploratory analyses of CIB subscales showed that whilst HC-G increased their reciprocal behavior during stress compared to the fun day planning, BPD-G dyads decreased it. Maternal ELM did not differ between groups or have any effect on behavior. Adolescent ELM was correlated with behavioral outcome variables, but did not explain behavioral outcomes above and beyond the effect of clinical status. DISCUSSION/CONCLUSION: Our data suggest a stronger focus on parent-child interactions in BPD-specific therapies to enhance long-term treatment outcomes in adolescent BPD patients. Further research employing study designs that allow the analyses of bidirectional transactions (e.g. longitudinal design, behavioral microcoding) is needed.